Problematika Guru dalam Pembelajaran pada Anak Berkebutuhan Khusus di TKIT Ar Rajwaa Samarinda - Khoirunnisa, Khoirunnisa; Saugi, Wildan; Sunanik, Sunanik (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
This study aims to examine the challenges faced by teachers in the learning process of children with special needs (CWSN) at TKIT Ar Rajwaa Samarinda. CWSN, such as children with Autism Spectrum Disorder (ASD), Attention Deficit Hyperactivity Disorder (ADHD), and speech delay, require special attention and approaches, particularly in early childhood education. This research employed a qualitative approach using a descriptive method. Data were collected through observation, interviews, and documentation, and were analyzed using the interactive model by Miles and Huberman. The validity of the data was tested through triangulation of techniques and sources to ensure the credibility of the findings. This study not only outlines the obstacles encountered by teachers, such as limited understanding, difficulties in managing inclusive classrooms, communication barriers, challenging behaviors, inadequate facilities, and difficulties in implementing individualized lesson plans, but also describes the practical strategies adopted by teachers, including direct observation, self-initiated training, and learning modifications. These findings contribute to the development of inclusive education practices in Islamic-based institutions and enrich the literature on handling CWSN in early childhood settings, particularly as a reference for teachers, educational institutions, and policymakers in designing inclusive learning strategies.